2015
DOI: 10.1073/pnas.1506781112
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli coculture systems for the production of biochemical products

Abstract: Engineering microbial consortia to express complex biosynthetic pathways efficiently for the production of valuable compounds is a promising approach for metabolic engineering and synthetic biology. Here, we report the design, optimization, and scale-up of an Escherichia coli-E. coli coculture that successfully overcomes fundamental microbial production limitations, such as high-level intermediate secretion and low-efficiency sugar mixture utilization. For the production of the important chemical cis,cis-mucon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(212 citation statements)
references
References 33 publications
4
206
0
2
Order By: Relevance
“…It has been previously shown that co‐culture engineering can provide important advantages in the production of important biochemicals . Here, we further show that co‐culture engineering can also facilitate effective selection of appropriate E. coli hosts that best accommodate a desired biosynthetic module.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…It has been previously shown that co‐culture engineering can provide important advantages in the production of important biochemicals . Here, we further show that co‐culture engineering can also facilitate effective selection of appropriate E. coli hosts that best accommodate a desired biosynthetic module.…”
Section: Resultssupporting
confidence: 58%
“…Both XL2‐Blue and XL10‐Gold have the chloramphenicol resistance genes integrated in the chromosome and were only transformed with pdc‐VS. All 10 transformed strains were co‐cultivated with E. coli P5.2 that had been previously engineered to provide DHS precursor . Plasmid pGro7 contained E. coli chaperone genes, but expression of these genes was completely un‐induced in this study.…”
Section: Methodsmentioning
confidence: 99%
“…One of the homologues (accession no. AAY57855) is organized in a BCD cluster and has been demonstrated to be highly oxygen-sensitive (5), whereas the other homologue (isomeric aroY-C [aroY-C iso ], AB479384) has been successfully utilized for cis,cis-muconic acid production in S. cerevisiae (5)(6)(7)(8) and E. coli (3,4,10,11). Contradictory results exist about the necessity to coexpress B (aroY-B; AAY57854) and D (aroY-D; AAY57856) genes to obtain decarboxylase activity in S. cerevisiae.…”
mentioning
confidence: 99%
“…Finally, Zhang and colleagues demonstrated how, by distributing a pathway across two E. coli modular cells, the natural secretion of a key pathway intermediate (i.e. 3‐dehydroshikimate) could be leveraged to improve the production of both 4‐hydroxybenzoic acid and cis , cis ‐muconic acid . In this case, to ensure stability of the co‐culture, one cell was engineered to import and consume only glucose and the other only xylose.…”
Section: Modular Engineering Strategies For Optimizing Pathway Flux Amentioning
confidence: 97%